2006
DOI: 10.1897/1551-3793(2006)2[204:esorea]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Significance of Residual Exposures and Effects from the Exxon Valdez Oil Spill

Abstract: An ecological significance framework is used to assess the ecological condition of Prince William Sound (PWS), Alaska, USA, in order to address the current management question: 17 y following the Exxon Valdez oil spill (EVOS), are there any remaining and continuing ecologically significant exposures or effects on the PWS ecosystem caused by EVOS? We examined the extensive scientific literature funded by the Exxon Valdez Trustees or by ExxonMobil to assess exposures and effects from EVOS. Criteria to assess eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 150 publications
(251 reference statements)
0
41
0
Order By: Relevance
“…Using the Gentile and Harwell (1998) criteria for assessing ecological significance (see also Harwell et al 1994), Harwell and Gentile (2006) evaluated a suite of approximately 2 dozen VECs that characterize the PWS ecosystem, concluding that by that point in time recovery had essentially occurred for almost all of the VECs; similar conclusions were presented in Integral Consulting (2006), with a few exceptions. However, the Exxon Valdez Oil Spill Trustees (EVOSTC 2010) continued to report several endpoints as not recovered, including characterizing sea otters and Harlequin Ducks as “recovering” but not yet recovered species.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Using the Gentile and Harwell (1998) criteria for assessing ecological significance (see also Harwell et al 1994), Harwell and Gentile (2006) evaluated a suite of approximately 2 dozen VECs that characterize the PWS ecosystem, concluding that by that point in time recovery had essentially occurred for almost all of the VECs; similar conclusions were presented in Integral Consulting (2006), with a few exceptions. However, the Exxon Valdez Oil Spill Trustees (EVOSTC 2010) continued to report several endpoints as not recovered, including characterizing sea otters and Harlequin Ducks as “recovering” but not yet recovered species.…”
Section: Introductionmentioning
confidence: 92%
“…In Harwell and Gentile (2006), we applied these concepts to assessing the significance of any continuing effects on the Prince William Sound (PWS), Alaska, ecosystem more than 15 years after the Exxon Valdez oil spill (EVOS) (see also Harwell, Gentile, Cummins et al 2010). In the ecological risk context, the issue is 2-fold, 1 pertaining to exposure and the other to effects: 1) Have the stressors caused by the oil spill decreased to the point where no further risk exists to the PWS ecosystem and its biota, and 2) Have VECs in PWS that were initially impacted now recovered?…”
Section: Introductionmentioning
confidence: 99%
“…Introduced by Beanlands and Duinker (1983) in Canada, VECs were recommended as a means to avoid the inefficient 'count everything' approach that characterized early IAs (Kennedy & Ross 1992;Treweek 1999). They were also meant to direct the focus of assessors to a more holistic view of ecological health and integrity (Harwell & Gentile 2006;Barnes et al 2010;Nunes 2010) rather than simply the effects of a particular development on 'just water' or 'just vegetation', for example (Beanlands & Duinker 1983). Similar processes exist outside the Canadian practice, e.g.…”
Section: Why Study Valued Ecosystem Component Selection?mentioning
confidence: 99%
“…A scan of the literature reveals some attention to the values that influence VEC choices, characterization of stressors affecting VECs, and application of the VEC concept within different assessment frameworks (see, for example, Lohani et al 1997;Harwell & Gentile 2006). In a recent review of project-based IAs in southern Saskatchewan, Ball et al (2013) found that aquatic VECs were usually selected to address a proponent's exposure to liability and penalty under federal legislation (e.g.…”
Section: Why Study Valued Ecosystem Component Selection?mentioning
confidence: 99%
“…67 They applied a risk assessment paradigm to evaluate a range of organisms from invertebrates to seabirds and marine mammals, and concluded that those resources not in decline at the time of the spill recovered within six years, with others approaching recovery by 15 years post-spill. Notable exceptions were those ecosystem attributes related to orca pods.…”
Section: Ecological Effects Of Oil Spillsmentioning
confidence: 99%